2015
DOI: 10.1002/aic.14747
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat transfer across the wall of dividing wall columns on energy demand

Abstract: The implementation of a vertical dividing wall (DW) into a distillation column is a well-known concept which can result in considerable energy savings for the separation of multicomponent mixtures. It is commonly known that heat streams across the DW, which are present due to temperature differences between both sides, may either increase or decrease the energy demand for a certain separation task. However, no work has been published so far which explains the maximum influence on energy demand. This article de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The advantages can only be realized in practice if a safe and stable operation is possible. As has been demonstrated, e.g., by Buck et al [13] and Ehlers et al [38], the nonreactive DWC can be controlled and operated very well. Preliminary studies by the authors of this article indicate for the RDWC that fluctuations in the vapor split and in the amount of component E can be handled by temperature control maintaining the desired CS E .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The advantages can only be realized in practice if a safe and stable operation is possible. As has been demonstrated, e.g., by Buck et al [13] and Ehlers et al [38], the nonreactive DWC can be controlled and operated very well. Preliminary studies by the authors of this article indicate for the RDWC that fluctuations in the vapor split and in the amount of component E can be handled by temperature control maintaining the desired CS E .…”
Section: Discussionmentioning
confidence: 68%
“…It has to be pointed out that the above-mentioned energysaving potential can only be realized when operating the DWC correctly. As Ehlers et al [38] demonstrate, a wrong operation of the DWC can lead to a much higher vapor demand in comparison to the conventional column sequences. This is due to a strong effect of the vapor split (VS) at the bottom and liquid split (LS) at the top of the dividing wall on the split of the components in the prefractionator.…”
Section: Process Fundamentalsmentioning
confidence: 99%
“…The value of the vapor split can be of very high importance in order to reach energy efficient column operation. Simulation‐based research studies showing the huge impact of the vapor split on the energy efficient operation of dividing wall columns are published by Fidkowski and Krolikowski, Halvorsen and Skogestad, and Ehlers et al In a recently published paper, Schröder et al show this strong influence for RDWCs as well. In reality, however, the vapor split can hardly be measured directly.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Jing et al [17] have proposed a heat transfer model of DWC, in which, the additional virtual intermediate heat exchangers are placed between the prefractionator and the main column, and thus the heat transfer process among the virtual intermediate heat exchangers will produce the thermal-coupled effect. Through a simple thought experiment and simulation study [18], it is concluded that the change in minimum energy demand of DWC cannot be more than the amount of heat which is transferred across the dividing wall.…”
Section: Introductionmentioning
confidence: 98%